cos2x + cos2(x + pi/3) + cos2(x - pi/3) = 3/2. prove

The above given explanation us correct.

  • -39

LHS = Cos2x + Cos2(x+^/3) + Cos2(x-^/3)

  = (1+cosx)1/2 + (1+cos(x+^/3))1/2 + (1+cos(x-^/3)) 1/2 

  = 1/2 ( 1+cosx + 1 +Cos(x+^/3) + 1 + Cos(x-^/3)  )

  = 1/2 ( 3 + cosx + Cos( x + 60 ) + Cos( x - 60)

.  = 1/2 ( 3 + Cosx + 2 cosx cos120)

  = 1/2 ( 3 + cosx + 2 cosx . -1/2)  (since  cos 120 = -1/2)

  = 1/2 ( 3 + cosx - cosx)

  = 3/2 = RHS

  here , ^ means "pi"

thumbs up please!!!

  • 120
What are you looking for?